2017
DOI: 10.1016/j.eti.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Technology options for faecal sludge management in developing countries: Benefits and revenue from reuse

Abstract: This article provides technology options for the treatment of Faecal Sludge (FS) in developing countries to minimise exposure to FS and assesses its benefits along with possible revenue generation from reuse. FS that is collected from septic tanks poses management challenges in urban areas of developing countries. Currently, FS is dumped into the urban and peri-urban environment, posing great risks to the soil, surface water and groundwater quality. FS treatment technology usually consists of (1) primary treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…Hence, future sanitation investments must incorporate the FS management to achieve safe excreta management, create added value for society while protecting human and ecosystem health, and promote sustainable development of urban environmental hygiene ( Andersson et al, 2016 ). Studies have shown that the potential market-value products from FS include dry sludge as a fuel for combustion, protein derived from sludge processing as animal feed, sludge as a component in building materials, biogas/biomethane, biochar, biodiesel, and compost from co-treatment of FS, and kitchen waste/organic waste as clean energy, biofuel, and soil conditioner ( Cheng et al, 2017 ; Diener et al, 2014 ; Krueger et al, 2020 ; Singh et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, future sanitation investments must incorporate the FS management to achieve safe excreta management, create added value for society while protecting human and ecosystem health, and promote sustainable development of urban environmental hygiene ( Andersson et al, 2016 ). Studies have shown that the potential market-value products from FS include dry sludge as a fuel for combustion, protein derived from sludge processing as animal feed, sludge as a component in building materials, biogas/biomethane, biochar, biodiesel, and compost from co-treatment of FS, and kitchen waste/organic waste as clean energy, biofuel, and soil conditioner ( Cheng et al, 2017 ; Diener et al, 2014 ; Krueger et al, 2020 ; Singh et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Elution X x x Shiba and Ntuli, 2017;Harder et al, 2019 Ammonia treatment X X X X Méndez et al, 2002;Nordin, 2010;Strande et al, 2014 Alkaline stabilization X X X X Bina et al, 2004;Strande et al, 2014;Anderson et al, 2015;Farrell et al, 2017 Thermal Carbonization X X X Strande et al, 2014;Harder et al, 2019 Incineration* X X X Rulkens, 2008;Diener et al, 2014;Strande et al, 2014 Pasteurization X X X Forbis-Stokes et al, 2016;Chapeyama et al, 2018;Septien et al, 2018 Solar drying X X X X Bennamoun, 2012;Strande et al, 2014;Singh et al, 2017 Physical-chemical Membrane nutrient extraction…”
Section: Nutrient-enriched Sorbent Materialsmentioning
confidence: 99%
“…An analysis of the qualitative costs and benefits for fecal sludge management in developing countries (Singh et al 2017) focused on the benefits of resource recovery and reuse. Table 22 demonstrates that a qualitative assessment of costs and benefits can still be a valuable tool when used to make preliminary decisions in a low resource environment.…”
Section: Qualitative Costs and Benefits Of Technology Options For Fecmentioning
confidence: 99%